In the consumer interest a selected history of consumer affairs in Australia 1945-2000 - Smith, Simon (Society of Consumer Affairs Professional in Business, 2000)
Charts the shifting responses of business and industry to consumer issues and consumer activism in the second half of the 20th century, and the evolving role of government as regulator. The book also celebrates the contributions made by consumer champions past and present whose achievements have benefitted all Australians.